PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK ELEKTRONIK BERORIENTASI KETERAMPILAN BERPIKIR KRITIS SEBAGAI SUMBER BELAJAR PADA MATERI SISTEM GERAK MANUSIA - Safitri, Tania; Natalina. L, Mariani; Darmadi, Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
The 2013 curriculum requires students to be able to develop thinking skills in the learning process, one of which is critical thinking skills. Critical thinking skills must be supported by the use of appropriate learning resources, namely electronic worksheets based on critical thinking skills on motion system material. This study aims to produce electronic student worksheets (LKPD) oriented to critical thinking skills as a learning resource on quality human motion system material. This research was conducted at the Biology Education Study Program, FKIP Riau University, SMA Negeri Plus Riau Province and SMA Negeri 1 Pekanbaru in February 2021 – September 2021. The subject of this research is basic competencies 3.4 human movement system material for class XI SMA. The type of research used is the ADDIE Research and Development model. The instrument used is a validation sheet. The validation sheet consists of 3 aspects, namely the content feasibility aspect, the pedagogic aspect and the design aspect. The average result of the validation of the electronic LKPD based on critical thinking skills based on the three aspects is 3.68 with a very valid category. These three aspects include content feasibility aspects with an average of 3.68, pedagogic aspects with an average of 3.57, design aspects with an average of 3.81. The aspect that gets the highest score is the design aspect with an average score of 3.81 which is in the very valid category. The results showed that the electronic LKPD oriented critical thinking skills as a learning resource on the human movement system material has been successfully developed and is of good quality and is feasible to be used as a learning resource.Key Words : Critical Thingking, Student Worksheets, ADDIE